Does economic growth attract FDI inflows? A dynamic panel analysis - Pascal L. Ghazalian (Economies, 2023)
Economic growth is deemed to be a conducive factor in attracting foreign direct investment (FDI) as it often confers location advantage to host countries and fosters business confidence. This paper examines the short-run and the long-run effects of economic growth on FDI inflows. The empirical analysis is conducted through the Generalized Method of Moments (GMM) System estimator for dynamic panel models. The main results show significant positive effects of economic growth on FDI inflows, and they indicate that the magnitudes of these effects are statistically comparable over time and do not diminish with higher economic growth levels. They also reveal important variations in the magnitude of these effects across geo-economic regions and over pertinent economic variables such as economic development level, international trade and foreign investment openness, and endowment in natural resources. These findings underscore the significance of developing growthenhancing policies that are designed on the basis of the economic and geo-economic characteristics of host countries. Such policies could be coupled with international trade and foreign investment openness directions to stimulate stronger responses of FDI inflows to economic growth and mitigate the implications of unfavorable global and regional political conditions.
Keywords: 330; economic growth; foreign direct investment; multinational enterprises; dynamic model; panel data